2018
DOI: 10.1136/openhrt-2017-000725
|View full text |Cite
|
Sign up to set email alerts
|

Role of ivabradine in management of stable angina in patients with different clinical profiles

Abstract: In chronic stable angina, elevated heart rate contributes to the development of symptoms and signs of myocardial ischaemia by increasing myocardial oxygen demand and reducing diastolic perfusion time. Accordingly, heart rate reduction is a well-known strategy for improving both symptoms of myocardial ischaemia and quality of life (QOL). The heart rate-reducing agent ivabradine, a direct and selective inhibitor of the I f current, decreases myocardial oxygen consumption while increasing diastolic time, without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
0
6
1
1
Order By: Relevance
“…8)15) The analysis of frequency of angina pectoris episodes compared to ranolazine showed diametrically opposed results in Taccheri et al 17) and Villano et al 19) Overall, there is no convincing evidence for significant advantages of ivabradine compared to other anti-anginal substances. We acknowledge that these results contrast current literature as Kaski et al 25) and Werdan et al, 26) who summarised that ivabradine represents a useful agent for the symptomatic treatment of patients with angina pectoris, even in relation to different subgroups as monotherapy, combination therapy, elderly, comorbidities, revascularisation and CAD without heart failure 25) as well as CCS classification, medical history and medication. 26) Their statements should be interpreted with caution as these reviews refer not only to RCTs but mainly to observational studies.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…8)15) The analysis of frequency of angina pectoris episodes compared to ranolazine showed diametrically opposed results in Taccheri et al 17) and Villano et al 19) Overall, there is no convincing evidence for significant advantages of ivabradine compared to other anti-anginal substances. We acknowledge that these results contrast current literature as Kaski et al 25) and Werdan et al, 26) who summarised that ivabradine represents a useful agent for the symptomatic treatment of patients with angina pectoris, even in relation to different subgroups as monotherapy, combination therapy, elderly, comorbidities, revascularisation and CAD without heart failure 25) as well as CCS classification, medical history and medication. 26) Their statements should be interpreted with caution as these reviews refer not only to RCTs but mainly to observational studies.…”
Section: Discussioncontrasting
confidence: 94%
“…24) This conclusion is also supported by the consensus statement of Ferrari et al 30) emphasising the synergistic effects of beta-blockers and ivabradine. In contrast to Kaski et al 25) and Werdan et al, 26) latter draws its statements from RCTs 7) 8) 11) 12) 27) 29) demonstrating—similar to the data which current guidelines 1) 2) 3) are based—that there is a great lack of randomised, double-blind, investigator-initiated studies with patient-centred, functional outcomes in an adequately large patient population.…”
Section: Discussionmentioning
confidence: 94%
“…Ivabradine effectively reduced the HR in patients with HF who were previously on beta-blocker therapy. 51 In patients whose HR was >70 bpm, addition of ivabradine to the beta-blocker was favorable. In the ETHIC-AHF trial, early co-administration of ivabradine and betablockers was found to be beneficial.…”
Section: Role Of Ivabradine In Patients With Stable Angina and Heart Failurementioning
confidence: 99%
“…Антиангинальная и противоишемическая эффективность селективного ингибитора If-каналов ивабрадина установлена у пациентов со СС в монотерапии и в комбинации с другими антиангинальными препаратами, включая БАБ [16,17]. Результаты исследования BEAUTIFUL [2] показали, что ивабрадин, назначенный в дополнение к стандартной терапии, способствует снижению риска сердечно-сосудистых событий у больных со стабильной ИБС и сердечной недостаточностью с низкой фракцией выброса [2], особенно у больных с исходной ЧСС >70 уд / мин и у пациентов с сохраняющимися приступами стенокардии [18].…”
Section: результатыunclassified